Discriminatory Practices in School Environment and Their Elimination Through School Mediation in Slovakia - Vanková, Katarína (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2020)
Teaching about human rights and freedoms means teaching about human dignity, tolerance between people, acceptance of people as they are, justice, equality, self-control, and self-assertiveness. Not to allow unfairness, deception, injustice, inequality, the humiliation of oneself and others. Tolerance in the school environment includes the acceptance of different views, different behaviors, a different relationship, but also toleration and patience in relation to others. A pupil who is unable to cope with conflicts is unable to adapt to changes and risks his own decline. The main problem is not that there are conflicts between us, but in the way how we respond to them, how we can deal with them, and what we do to prevent them, or what we do to successfully resolve them. Conflicts in the school environment are a natural part of school life, indicating, in particular, the presence of differences. Conflict resolution through school mediation represents the ability to not only perceive, understand but particularly respond to and resolve conflict situations with the help of a third neutral person. School and peer mediation can be a way how to teach pupils to develop strong friendships, even in an environment of diversity and differences; it can be a preparation for inclusive educational system.